The use of sail for pre-Hispanic navigation off the Peruvian coast and its importance in the Andean world - Ruiz Romero, Javier Erison (2022)
The main goal of the research was to study the use of pre-Hispanic sails and its implications in indigenous navigation. The iconographic analysis, the corresponding ethnohistorical and ethnographic study were carried out. It was concluded that in 1100 AD new figures appear represented in the iconography of the Central Andes; these are the log rafts with mast and sail, which correspond mainly to the Lambayeque and Chimú cultures. Many of these sails have a triangular design, also called latinas, which are ideal for sailing with headwinds. In the 16th century the main area of the sailing log rafts extended from Manta in Ecuador to the north coast of Peru, from Tumbes to Sechura; tradition that must have originated centuries before the arrival of the Spanish, expanding further south allowing the navigation of the Lambayeque and Chimú cultures to Ecuador.